1952
DOI: 10.1017/s0021859600056896
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the breeding season and reproduction of the ewe Part I. The breeding season in different environments Part II. The breeding season in one locality

Abstract: A knowledge of the exact length of the breeding season for improved breeds under different environmental conditions in this country is lacking. Such knowledge is of importance so that the lambing season can be arranged according to farm conditions. Such knowledge, apart from providing the necessary background for the successful application of artificial insemination and administration of hormones, helps to explain certain problems of infertility. By selection it should be possible to build up strains, by exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
2

Year Published

1969
1969
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 317 publications
(60 citation statements)
references
References 0 publications
5
53
2
Order By: Relevance
“…Although the affiliation between the European mouflon and the domestic sheep's wild ancestor is not straightforward due to a complex history of fertilization and hybridization between wild and domestic populations (Poplin, 1979;Schröder et al, 2016), the European mouflon remains the closest living representative of early domestic breeds. A 3-to 4-month period is also longer than what was observed in the 8th millennium BC domestic sheep in the Near East (Tornero et al, 2016), while it is shorter than what is observed in most improved breeds (Hafez, 1952). This corroborates the idea that domestication led to an extension of the period of sexual activity in sheep (Hafez, 1952), but also that this trend was accentuated over the long term.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Although the affiliation between the European mouflon and the domestic sheep's wild ancestor is not straightforward due to a complex history of fertilization and hybridization between wild and domestic populations (Poplin, 1979;Schröder et al, 2016), the European mouflon remains the closest living representative of early domestic breeds. A 3-to 4-month period is also longer than what was observed in the 8th millennium BC domestic sheep in the Near East (Tornero et al, 2016), while it is shorter than what is observed in most improved breeds (Hafez, 1952). This corroborates the idea that domestication led to an extension of the period of sexual activity in sheep (Hafez, 1952), but also that this trend was accentuated over the long term.…”
Section: Discussionsupporting
confidence: 78%
“…The duration of the period of births is estimated tõ 3 to 4 months (Figures 3 and 4). This is significantly higher than what is observed today in the European mouflon, where births occur during a period of only 1 to 2 months (Hafez, 1952;Pfeffer, 1967;Garel et al, 2005;Tornero et al, 2016). Although the affiliation between the European mouflon and the domestic sheep's wild ancestor is not straightforward due to a complex history of fertilization and hybridization between wild and domestic populations (Poplin, 1979;Schröder et al, 2016), the European mouflon remains the closest living representative of early domestic breeds.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations